2021
DOI: 10.1038/s41594-021-00572-y
|View full text |Cite
|
Sign up to set email alerts
|

A first exon termination checkpoint preferentially suppresses extragenic transcription

Abstract: Interactions between the splicing machinery and RNA Polymerase II (RNA Pol II) increase protein-coding gene transcription. Similarly, exons and splicing signals of enhancer-generated lncRNAs (elncRNAs) augment enhancer activity. However, elncRNAs are inefficiently spliced, suggesting that compared to protein-coding genes they contain qualitatively different exons with a limited ability to drive splicing. We show here that the inefficiently spliced first exons of elncRNAs as well as promoter-antisense lncRNAs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 76 publications
5
45
0
Order By: Relevance
“…For example, ZC3H4, a CCCH zinc finger domain-containing RBP, occupies broad promoter regions and represses non-coding transcription events in human cells [ 27 ]. With WDR82 that binds Ser5-phosphorylated RNA Pol II, ZC3H4 forms a complex that suppresses lncRNAs transcribed from enhancers and promoters by transcription termination, which is activated by the inefficiently spliced first exon of lncRNAs [ 28 ]. Collectively, RBPs can function as regulatory proteins and control the expression of lncRNAs in multiple ways.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ZC3H4, a CCCH zinc finger domain-containing RBP, occupies broad promoter regions and represses non-coding transcription events in human cells [ 27 ]. With WDR82 that binds Ser5-phosphorylated RNA Pol II, ZC3H4 forms a complex that suppresses lncRNAs transcribed from enhancers and promoters by transcription termination, which is activated by the inefficiently spliced first exon of lncRNAs [ 28 ]. Collectively, RBPs can function as regulatory proteins and control the expression of lncRNAs in multiple ways.…”
Section: Introductionmentioning
confidence: 99%
“…This observed positive correlation might also be explained by effects of splicing on nuclear export [ 43 ], or on RNA stability [ 40 , 44 ], that can both enhance steady-state RNA levels per gene. Additionally, it was shown that splicing and transcription occur simultaneously [ 13 ], and it was recently demonstrated in mammalian cells that inefficient splicing of non-coding RNA can lead to transcription termination [ 45 ]. In addition, this correlation could be explained by an effect of transcription rate on splicing but we estimate that this explanation is less likely since all variants in the library are transcribed using the same promoter.…”
Section: Resultsmentioning
confidence: 99%
“…However, we show that the effect of 5'SSs goes beyond this role, to stimulate transcription more broadly. We propose that changes in RNAPII conformation that occur upon U1 binding make it intrinsically more processive, and/or prevent association of other termination machineries, such as Integrator 2,41 and WDR82/ZC3H4 42,43 . Providing a molecular mechanism for 5'SS-mediated transcription stimulation and identifying additional sequence elements that regulate transcription elongation will be important for future work, and we anticipate that our newly developed methodology can be leveraged towards these goals.…”
Section: Discussionmentioning
confidence: 99%